An Analysis of the Relationship Between Tourism and Environmental Pollution in Southwest China - Hong Li (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The present study explores the relationship between tourism and environmental pollution in southwest China using the panel data from 1995 to 2017, taking the annual tourist arrivals and carbon emission as the main variables, based on immense tourism market and severe environmental problems in China. Southwest region is less developed but important part of China, and holds rich tourism resources. Panel ARDL technique is applied in this study and Kink Regression is employed to test whether tourism-induced EKC hypothesis exists in Southwest China. The results indicate that tourism-induced EKC hypothesis exists Yunnan and Sichuan provinces. And the estimation results show that there is a positive impact of tourism on the environment in southwest provinces. The coefficient of tourism is negative, indicating that tourism sector assists in reducing the level of carbon emission and improve the environmental quality. Similarly, trade openness tends to induce the carbon emission and benefit for the environment. Conversely, the coefficients of energy consumption and GDP show that both of the variables have a negative impact on environment.